2010
DOI: 10.1016/j.fuproc.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic char reactivity of plastic waste (PET) during CO2 gasification

Abstract: Char reactivity has a strong influence on the gasification process, since char gasification is the slowest step in the process. A sample of waste PET was devolatilised in a vertical quartz reactor and the resulting char was partially gasified under a CO 2 atmosphere at 925 ºC in order to obtain samples with different degrees of conversion. The reactivity of the char in CO 2 was determined by isothermal thermogravimetric analysis at different temperatures in a kinetically controlled regime and its reactive beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The plots of the non-dimensional rates were more convex than those of the volume reaction model (dotted line). In this case, the random pore model (RPM) was applied to estimate the CO 2 gasification rates of the chars (Bhatia and Perlmetter, 1980, Gil, et al, 2010, Yuan, et al, 2011. In cases where a drastic increase in the non-dimensional rate is observed at high carbon conversion (X > 0.6) during the CO 2 gasification of metal-loaded chars, the extended random pore model (eRPM) is usually applied to estimate the gasification rates (Tancredi, et al, 1996, Marques, et al, 2002, Zhang, et al, 2008, Kopyscinski, et al, 2013.…”
Section: Measurement Of the Co 2 Gasification Reactivity Of The Charsmentioning
confidence: 99%
“…The plots of the non-dimensional rates were more convex than those of the volume reaction model (dotted line). In this case, the random pore model (RPM) was applied to estimate the CO 2 gasification rates of the chars (Bhatia and Perlmetter, 1980, Gil, et al, 2010, Yuan, et al, 2011. In cases where a drastic increase in the non-dimensional rate is observed at high carbon conversion (X > 0.6) during the CO 2 gasification of metal-loaded chars, the extended random pore model (eRPM) is usually applied to estimate the gasification rates (Tancredi, et al, 1996, Marques, et al, 2002, Zhang, et al, 2008, Kopyscinski, et al, 2013.…”
Section: Measurement Of the Co 2 Gasification Reactivity Of The Charsmentioning
confidence: 99%
“…One of the most important varying intrinsic properties of the char that influence its gasification rate is char physical structure. Many studies intended to correlate char physical structure properties and their changes with the char conversion rate . Char reactivity has been correlated to such structural properties as the specific surface area, mesopore volume, and carbon crystalline structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers aimed to correlate the reaction rate with the specific surface areas derived from the conventional physical adsorption techniques. Several studies have not revealed a direct linear correlation between the gasification rate and char specific surface area determined by the Brunauer‐Emmett‐Teller (BET) method . There was also no obvious correlation observed between char reactivities and the carbon crystalline structure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, for different biomass and coals char containing various amount of alkali and alkaline metal contents, their gasification performance are totally different. However, there are few alkali and alkaline metals exist in the WEEE plastic chars and few attempts have been made to investigate the CO 2 gasification reactivity of WEEE plastic chars derived from the medium-temperature pyrolysis (Gil, Fermoso, Pevida, Pis & Rubiera 2010). Additionally, the CO 2 gasification reactivity of chars is lower than that of O 2 or H 2 O gasification, and consequently, it is regarded as the rate-determining step in the gasification process .…”
Section: Introductionmentioning
confidence: 99%